MANDATORY VACCINATION COVERAGE IN THE TERRITORY OF THE MAČVA DISTRICT IN THE PERIOD BETWEEN 2011 AND 2021 - Pajičić, Ana; Jović-Vraneš, Aleksandra; Vujković Brankо (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: The vaccine is one of medicine’s oldest and most valuable inventions. It is a simple, safe, and effective way to protect against infectious diseases, a proven and cost-effective public health strategy that safeguards both individuals and the entire community. On the other hand, it has become a victim of its own success, as many vaccine-preventable diseases have become so rare that some people believe they have been eradicated forever, and do not understand the benefits of vaccination nor the risks of it not being conducted. This study aimed to analyze vaccination coverage throughout the Mačva District, in the period between 2011 and 2021. Materials and methods: The study used a retrospective analysis of secondary data from annual reports submitted by community health centers, in the territory of the Mačva District, for the period between 2011 and 2021. For the purpose of this study, vaccination coverage was calculated based on the number of newborn babies in a given year. Data from community health centers are submitted to the Institute of Public Health Šabac, which is in charge of these issues for this district. Each report contains the number of individuals subject to mandatory immunization, the number of persons who have been vaccinated, as well as the percentage of vaccinated persons as compared to the number of persons who should have been vaccinated. The correlation and regression method was used to analyze the vaccination trend, i.e., the value of the Pearson correlation coefficient was interpreted and the equation of the regression line was calculated. Results: In the Mačva District, mandatory vaccination coverage of children was observed in the period between 2011 and 2021. A negative trend was registered in vaccination coverage for all observed vaccines, except the trend related to vaccination for Haemophilus influenzae. Conclusion: When all of the vaccines are observed together, vaccination coverage has been declining during the observed period. During 2021, not a single vaccine achieved 95% coverage. The declining trend indicates the need to promote vaccination as the safest and most effective protection against infectious diseases.